Augmenting Interactive Tables with Mice & Keyboards - Hartmann, Bjoern; Morris, Meredith Ringel; Benko, Hrvoje; Wilson, Andy (Microsoft, 2009)
This note examines the role traditional input devices can play in surface computing. Mice and keyboards can en-hance tabletop technologies since they support high fidelity input, facilitate interaction with distant objects, and serve as a proxy for user identity and position. Interactive tabletops, in turn, can enhance the functionality of traditional input devices: they provide spatial sensing, augment devices with co-located visual content, and support connections among a plurality of devices. We introduce eight interaction techniques for a table with mice and keyboards, and we discuss the design space of such interactions.
To appear in the Proceedings of UIST 2009.